Research Engagement: A Participatory Approach of Learning for Public School Teachers - Usita, Maricris (CV. Inara, 2022)
Teacher research participation in pedagogy advancement, personal growth, and professional development provides a wide range of benefits. This paper aims to assess the teacher research engagement and learning based on the extended intervention program conducted by Occidental Mindoro State College – Graduate Scholl Unit by determining its relevance, planning, implementation, resources, monitoring, and evaluation. The analysis presented the strategies, intervention, effectiveness and challenges, lessons learned, and contributory factors gained by the participants as part of the training program of the Department of Education - Calintaan district. Results revealed that the concluded intervention program in research capability was very effective, indicating that it helped teachers enhance their research engagement.